No association between the angiotensin-converting enzyme ID polymorphism and elite endurance athlete status - Rankinen, T.; Wolfarth, B.; Simoneau, J. A.; Maier-Lenz, D.; Rauramaa, R.; Rivera, M. A.; Boulay, M. R.; Chagnon, Y. C.; Perusse, L.; Keul, J.; Bouchard, C. (Journal of Applied Physiology, 2000)
Several studies have reported that the insertion (I) allele of the angiotensin-converting enzyme (ACE) I/deletion (D) polymorphism is associated with enhanced responsiveness to endurance training and is more common in endurance athletes than in sedentary controls. We tested the latter hypothesis in a cohort of 192 male endurance athletes with maximal oxygen uptake 75 ml · kg1 · min1 and 189 sedentary male controls. The ACE ID polymorphism in intron 16 was typed with the three-primer polymerase chain reaction method. Both the genotype (P = 0.214) and allele (P = 0.095) frequencies were similar in the athletes and the controls. Further analyses in the athletes revealed no excess of the I allele among the athletes within the highest quartile (> 80 ml · kg1 · min1) or decile (>83 ml · kg1 · min 1) of maximal oxygen uptake. These data from the GENATHLETE cohort do not support the hypothesis that the ACE ID polymorphism is associated with a higher cardiorespiratory endurance performance level.